Inflammatory intrathecal profiles and cortical damage in multiple sclerosis - Magliozzi,R; Howell,OW; Nicholas,R; Cruciani,C; Castellaro,M; Romualdi,C; Rossi,S; Pitteri,M; Benedetti,MD; Gajofatto,A; Pizzini,FB; Montemezzi,S; et al. (Annals of Neurology, 2018)
OBJECTIVE: Grey matter (GM) damage and meningeal inflammation have been associated with early disease onset and a more aggressive disease course in Multiple Sclerosis (MS), but can these changes be identified in the patient early in the disease course? METHODS: To identify possible biomarkers linking meningeal inflammation, GM damage and disease severity, gene and protein expression were analysed in meninges and CSF from 27 post-mortem secondary progressive MS (SPMS) and 14 control cases. Combined cytokine/chemokine CSF profiling and 3T-MRI were performed at diagnosis in two independent cohorts of MS patients (35 and 38 subjects) and in 26 non-MS patients. RESULTS: Increased expression of pro-inflammatory cytokines (IFNγ, TNF, IL2 and IL22) and molecules related to sustained B-cell activity and lymphoid-neogenesis (CXCL13, CXCL10, LTα, IL6, IL10) was detected in the meninges and CSF of post-mortem MS cases with high levels of meningeal inflammation and GM demyelination. Similar pro-inflammatory patterns, including increased levels of CXCL13, TNF, IFNγ, CXCL12, IL6, IL8 and IL10, together with high levels of BAFF, APRIL, LIGHT, TWEAK, sTNFR1, sCD163, MMP2 and pentraxin III, were detected in the CSF of MS patients with higher levels of GM damage at diagnosis. INTERPRETATION: A common pattern of intrathecal (meninges and CSF) inflammatory profile strongly correlates with increased cortical pathology, both at time of the diagnosis and of death. These results suggest a role for detailed CSF analysis combined with MRI, as a prognostic marker for more aggressive MS. This article is protected by copyright. All rights reserved.